CHARACTERISTICS OF FREE SURFACE OF HOT STRANGE QUARK MATTER - Alaverdyan, A.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
Within the framework of MIT bag model, properties of hot strange quark matter at zero pressure are investigated. It is shown that the self-boundness property of strange quark matter has a temperature dependent character. With increasing temperature, the strange quark matter which is self-bound at zero temperature, starting with a certain critical temperature becomes not self-bound.